From 'science in the making' to understanding the nature of science : an overview for science educators - Niaz, Mansoor (New York : Routledge, 2012)
"The Nature of Science is highly topical among science teacher educators and researchers. Increasingly, it is a mandated topic in state curriculum documents. This book draws together recent research on Nature of Science studies within a historical and philosophical framework suitable for students and teacher educators. Traditional science curricula and textbooks present science as a finished product. Taking a different approach, this book provides a glimpse of "science in the making" -- scientific practice imbued with arguments, controversies, and competition among rival theories and explanations"-- Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Science -- Study and teaching; Science teachers -- Training of; Electronic books